2021
DOI: 10.1186/s12872-021-02155-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of creatine kinase MB for contrast-induced acute kidney injury among myocardial infarction patients

Abstract: Background Predictive value of creatine kinase MB (CK-MB) for contrast-induced acute kidney injury (CI-AKI) among myocardial infarction (MI) patients has rarely been reported. We aim to evaluate the predictive value of CK-MB for CI-AKI among MI patients. Methods Totally, 1131 MI patients were included from the REduction of rIsk for Contrast-Induced Nephropathy (REICIN) study. The peak CK-MB before coronary angiography (CAG) was chosen. The study po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In addition, Hsu et al [ 51 ] proved that, in patients with AMI, early peak CK-MB levels (cut-off 48.2 ng/mL) were associated with an increased risk for adverse cardiac remodeling within six months after discharge. Additionally, patients with log-transformed CK-MB values greater than 4.7 had a 3.4-fold higher incidence of CIN than those without [ 102 ]. Peak CK-MB showed a strong association with chronic scar dimension and chronic wall motion abnormality index in patients with non-transmural myocardial infarction undergoing PCI or coronary artery bypass graft surgery (CABG) [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Hsu et al [ 51 ] proved that, in patients with AMI, early peak CK-MB levels (cut-off 48.2 ng/mL) were associated with an increased risk for adverse cardiac remodeling within six months after discharge. Additionally, patients with log-transformed CK-MB values greater than 4.7 had a 3.4-fold higher incidence of CIN than those without [ 102 ]. Peak CK-MB showed a strong association with chronic scar dimension and chronic wall motion abnormality index in patients with non-transmural myocardial infarction undergoing PCI or coronary artery bypass graft surgery (CABG) [ 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings are also consistent with previous research. 27,28 The H 2 FPEF score is used to diagnose HFpEF and for the differential diagnosis of cardiac and non-cardiac dyspnea. 9 With this scoring system, the diagnosis of HFpEF has become easier.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, CK-MB plays an essential role in the diagnosis of acute coronary syndrome [8] . Moreover, an elevated serum level of CK-MB is associated with poor prognosis of COVID-19 [9,10] and provides a predictive value for contrast-induced acute kidney injury among myocardial infarction patients [11] . In addition, studies have also found that CK-MB is associated with the in-hospital mortality of polytrauma patients [4,12] .…”
Section: Introductionmentioning
confidence: 99%